University educational model: conceptual approaches - Zamora Serrano, Evelyn (2026)
This essay examines the concept of a university educational model from a critical theory perspective, analyzing the existing conceptual diversity in the literature and the limitations this diversity imposes on its understanding, formulation, and application. It argues that defining an educational model is essential for guiding university policies, academic work, and the social relevance of higher education. The analysis is based on the notion of an educational model as a theoretical framework that comprehensively represents university reality through the interrelation of philosophical, pedagogical, curricular, and organizational components. Furthermore, it discusses the conceptual distinction between model, paradigm, and theory as a necessary condition for overcoming persistent theoretical ambiguities. As its main contribution, the essay proposes conceptualizing the university educational model as a theoretical representation of educational reality within a specific context, in which subjects and objects interact through moral, psychological, communicative, cultural, sociological, economic, and political processes. It is concluded that the educational model possesses transformative potential at both the institutional and social levels, influencing the construction of educational meanings, academic practices, and university decision-making processes. Therefore, this work constitutes a framework that can be operationalized in future empirical research aimed at testing this theoretical proposal in specific university contexts.